DIGITALISASI DESAWISATA BERBASIS KOMUNITAS MELALUI INSTAGRAM @DEWITINALAH: KAJIAN ANALISIS MULTIMODAL KRESS DAN VAN LEEUWEN - Eko Agung Sugiyarto; Marlinda Irwanti Poernomo; Maryami (JURNAL KOMUNITAS, 2026)
Sustainable tourism supported by the government and based on the empowerment of local communities is known as ecotourism. The Tinalah Village Tourism Destination uses Instagram as an online promotional tool. As defined by the International Ecotourism Society (TIES), promotional content for tourism villages must reflect the characteristics of the village so that tourists not only receive information about tourism but also understand the values of conservation, education, and community participation which are the primary objectives of tourism villages. Using Kress and van Leeuwen’s multimodal analysis approach, this study aims to describe the characteristics of the tourism village from a TIES perspective as presented in Instagram promotional content. The study conducted a content analysis of posts on the @dewitinalah Instagram account using a descriptive qualitative approach. The results indicate that the promotional content on this account possesses representational, interactive, and compositional meanings related to the characteristics of a tourism village according to TIES. These meanings are evident in the promotional, educational, historical, and knowledge-based content presented in the feed. However, the management of digital promotional content still needs improvement through training for the local community, particularly regarding how to optimize digital promotional content. This effort is crucial for sustainable tourism goals, as tourism villages enable optimal growth and global competitiveness..